A Dynamic Model for Strategies and Dynamics of Plant Water-Potential Regulation Under Drought Conditions - Papastefanou, Phillip; Zang, Christian S.; Pugh, Thomas A. M.; Liu, Daijun; Grams, Thorsten E. E.; Hickler, Thomas; Rammig, Anja (Frontiers in Plant Science, 2020)
Vegetation responds to drought through a complex interplay of plant hydraulic mechanisms, posing challenges for model development and parameterization. We present a mathematical model that describes the dynamics of leaf water-potential over time while considering different strategies by which plant species regulate their water-potentials. The model has two parameters: the parameter λ describing the adjustment of the leaf water potential to changes in soil water potential, and the parameter Δψ_max describing the typical leaf water potentials at non-stressed (near-zero) levels of soil water potential. Our model was tested and calibrated on 70 time-series datasets containing the leaf- and soil water potentials of 50 species under drought and non-drought conditions. Our model successfully reproduces the measured leaf water potentials over time based on three different regulation strategies under drought. We found that one parameter set derived from the measurement data reproduced the dynamics of 62% of an available validation-drought dataset, and 58% of a control dataset [root mean square error (RMSE) < 0.5 MPa)]. We conclude that, instead of quantifying water-potential-regulation of different plant species by complex modelling approaches, a small set of parameters may be sufficient to describe the water potential regulation behavior for large-scale modelling. Thus, our approach paves the way for a parsimonious representation of the full spectrum of plant hydraulic responses to drought in dynamic vegetation models.